Efeitos positivos do uso de brincadeiras ativas para aprendizagem de conte??dos escolares e a cogni????o de crian??as - Ramos, Isabela Almeida (2017)
Learning difficulties and disturbs, socioeconomic conditions, could justify the high rate of brazilian educational system failure. Therefore, interdisciplinary Physical Education can ameliorate children learning. The purpose of this study was to verify the effects of an interdisciplinary physical education program on academic achievement and selective attention in children. 60 boys and girls from 4th grade of public elementary brazilian school, underwent a Education by Movement group (EduMove) (n=39, 9.7??yr; 31.6 ?? 6.2 kg; 1.4 ?? 0.1 m; 17.9 ?? 7.2 %G) with math, written and reading classes through physical education activities during a school journey (172.8??16.31bpm) (60min each class, twice a week), and a control group (Con) (n=21, 9.9??0.8yr; 30.0 ?? 5.1 kg; 1.4 ?? 0.1 m; 17.1 ?? 8.6 %G) which participated at traditional classes (92.4??8.9bpm). Thereafter children undertook anthropometric (weight, height, body fat), physical activity level, academic achievement, selective attention test (Stroop Go/NoGo), before and after three months. ANOVA revealed tricipital skinfold reduction for EduMove in comparison with CON at post test (11.8 ?? 5.6 vs 12.7 ?? 5.3; p=0.008), it was observed higher physical activity level for EduMovi vs CON (?? 23.3 vs 2.9 METs; p=0.09). Children showed better results at reading capacity for EduMovi vs CON (65.2 ?? 4.9 vs 64.7 ?? 3.0; p=0.038). Regarding selective attention EduMovi was faster and committed less mistakes in comparison with pre test (236.1 ?? 39.9 vs 327.9 ?? 45.88 ms/%, ?? -90ms e - 2% de erros p=0.09). A short term interdisciplinary physical education program can improve reading capacity, and selective attention in children. These results may suggest that activity breaks during a school journey could contributing to learning.